Optimization of slope angles of a barge-shaped FPSO from the towing stability and load perspective - Chang Seop Kwon (Elsevier, 2021)
In this study, a parametric investigation is performed using CFD for towing stability and loads according to the forward and aft slope angles of a barge-shaped FPSO. The forward slope angle is considered in a range of 30–60° and the aft slope is examined in a range of 20–50°. As a result of a comparative study based on CFD towing simulations, it is found that the yaw motion is damped out and stabilized when the aft slope is more than 40° regardless of the forward slope angle. The vortex contours in the y-axis plane near the aft slope are analyzed and it is observed that the vortex developed at the bottom knuckle is bent upward along the aft slope when the aft slope is less than 40°, and completely fallen from the bottom knuckle when the aft slope is more than 40°. Based on the results, a guide to forward and aft slope angles of a barge-shaped FPSO is presented from a practical point of view considering towing stability as well as towing load.